Соціальний медіа маркетинг: сучасні тренди та перспективи розвитку - Балик, У. О.; Колісник, М. В.; Balyk, U.; Kolisnyk, M. (Видавництво Львівської політехніки, 2020)
Розкрито результати дослідження сутності соціальних мереж. Окремо вивчено стан розвитку соціальних мереж у світі загалом та в Україні зокрема. Проаналізовано потенційне охоплення рекламою у соціальних мережах. Розкрито особливості соціальної медіа-реклами. Представлено профіль рекламної аудиторії провідних соціальних мереж у розрізі вікових, гендерних та географічних ознак. Визначено ключові тренди та перспективи розвитку соціального медіа-маркетингу. Виявлено проблеми, з якими бояться стикнутися маркетологи у майбутньому, здійснюючи свою діяльність у соціальних мережах. Запропоновано напрями поліпшення роботи маркетологів у соціальних мережах.

Social networks have become an alternative and promising platform for advertising and establishing lively, active and mutually beneficial communication with customers online in the fastpaced world of digitalization. The purpose of the article is to reveal the features of social networks as a platform for marketing applications, to identify main trends and prospects of social media marketing development. The results of the study of the essence of social networks were revealed. The author separately explores the state of development of social networks in the world in general and Ukraine in particular. The article was established that today social networks are already a multi-billion dollar sector of the world economy. The potential reach of social media advertising in the world has been explored. The features of social media marketing were disclosed. In the modern sense, social media marketing has been found to be a form of internet marketing that uses social media platforms to engage with an audience in order to create and promote a brand, increase website traffic, customer reach and sales. There was presented advertising audience profile of the leading social networks by age, gender, and geographical characteristics. The author identified the main trends and prospects of social media marketing development. Recently, marketers have called image/video and narrative the most important aspects when creating and publishing a piece of content. Video advertisements are gaining in popularity and delivering positive returns to investors. There were especially relevant formats such as strimming, stories, IGTV. There was revealed that every year the number of businesses that do not create any video content on social networks is decreasing. Another clear trend is the growing popularity of messaging apps. Advertisements for these chat-bot applications have raised the level of communication in online business with clients and are quite promising. An increase in the position of influencer marketing in the strategy of development of social networks of enterprises is revealed. However, social media users' trust in the advertising that influencers with a large number of subscribers have been observing has recently been undermined. Instead, influencers with fewer subscribers are more attractive to marketers and consumers. The problems that marketers are afraid to face in the future when conducting their activities on social networks were highlighted. Prospects for further research include exploring the problems that deter marketers from advertising on social networks and finding ways to solve them.
Social media marketing: current trends and prospects of development
Keywords: соціальні мережі; реклама; маркетинг; стратегія; діджиталізація; social networks; advertising; marketing; strategy; digitization; М; 30; О; 14; 339.138